Evaluasi berbagai Karakter Agronomi Kedelai (Glycine max [L.] Merrill) pada Galur F7 Hasil Persilangan Grobogan dengan KM 25 Evaluationof Various Agronomic Charactersof Soybean(Glycine max [L.] Merrill) in F7LinesfromGrobogan Crossingwith KM25 - Dwi, Rani Novia; Deviona, Deviona; Zuhry, Elza (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2021)
The objective of this study was to evaluate various agronomic characters of soybean in F7 line from Grobogan crossing with KM25 for the potential line for F8 line. A total of ten genotypes were planted consisting of eight from F7 lines and two comparison parents (Grobogan and KM 25). The changes that observed were age of flowering, age of harvest, plant height, number of primary branches, number of pods per plant, number of pithy pods, number of seeds per plant, weight of seeds per plant, weight of 100 seeds, weight of seeds per m2, weight of plants per plot, and index of harvest. Data were analyzed statistically use SAS and the results of analysis of variance followed by test of dunnett level 5%. Analysis of variance shows that there are significant differences between F7 lines of soybean and comparison parents in age of flowering, age of harvest, plant of height, number of pods per plant, number of pithy pods per plant, weigh of seeds per plant, weight of 100 seeds, weigh of seed per m2, weight of plants per plot and index of harvest. The character of weight of seeds per plant has a wide diversity value because it is twice higher than the error standard. The characters that belongs into the group of high heritability values are number of pods per plant, number of pithy pods per plant, number of seeds per plant, weight of seeds per m2, weight of plants per plot and index of harvest. The highest selection value is on weight of plants per plot. The character with high crops and age of early maturity can be used as criteria for selecting new superior variety. keywords : soybean, agronomic characters, Grobogan, KM 25